Technology and Innovative Ambidexterity Towards Digital Infrastructure Development in Indonesia - Resty, Farrah Tya; Aziz, Yudi; Kaltum, Umi (CSID Journal of Infrastructure Development, 2019)
The increasingly rapid industrial environment triggers companies to explore their potential optimally, one of them is with technology. Based on the report of the World Economic Forum (WEF) on the 2017-2018 Global Competitiveness Index, it states that Indonesia's global competitiveness index is 45th out of 140 countries. In 2030, Indonesia is targeted to become the fourth-largest economy in the world. One way is to revitalize Indonesia's manufacturing sector in the industry 4.0 phenomenon, namely through technological developments. The company must continue to innovative ambidexterity to survive in this rapidly changing environment. This technology development and innovative ambidexterity planning are prepared to avoid the complexity of developing digital infrastructure in Indonesia. Therefore, Indonesia is expected to be able to prepare plans for managing the analysis, design and development of systems to support and implement the Industrial Revolution 4.0.